Efficacy of Household and Commercial Washing Agents in Removing the Pesticide Thiabendazole Residues from Fruits - Xinyi Du; Lauren Ho; Sisheng Li; Jeffery Doherty; Junghak Lee; John M. Clark; Lili He (Foods)
Pesticide residues on fruits pose a global food safety concern, emphasizing the need for effective and practical removal strategies to ensure safe consumption. This study investigates the efficacy of household ingredients (corn starch, all-purpose flour, rice flour and baking soda) and four commercial fresh produce wash products in eliminating a model pesticide thiabendazole with and without a model non-ionic surfactant Alligare 90® from postharvest fruits. Surface-enhanced Raman spectroscopy (SERS) was employed for the rapid, in situ quantification of residue removal on apple surfaces. Soaking in 2% corn starch followed by soaking in 5% baking was the most effective homemade strategy, removing 94.13% and 91.78% of thiabendazole with and without the surfactant. Among commercial washing agents, soaking in 2% Product 4 demonstrated the highest efficiency, removing 95.3% and 95.99% of thiabendazole with and without surfactant. These results suggested that the non-ionic surfactant did not affect removal efficiency. Both protocols were effective across various fruits (apples, grapes, lemons, strawberries), validated by liquid chromatography–mass spectrometry (LC-MS/MS) analyses. However, safety concerns regarding the composition of Product 4 highlighted the benefits of homemade strategies. Overall, this work offers practical guidelines for reducing pesticide residues on fruits and enhancing food.